Preliminary - Gómez Botero, Maryory Astrid; Palacio Tobón, Carlos Alberto (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
For ages, men have used writing to preserve and spread knowledge, which has allowed that generations and complete epochs have been able to be discovered and rediscovered by scientists, scholars, and researchers from all subsequent times. Scientific publications are “the machine of the time” that make the dialogue of sciences among different periods possible.